3. Handel międzynarodowy Kirgistanu – najważniejsi partnerzy, kluczowe produkty eksportowe i importowe .......... 123 - Dujka, Patryk (Kirgistan – oblicza transformacji, 2020)
INTERNATIONAL TRADE IN KYRGYZSTANThe article presents the strengths and weaknesses of Kyrgyzstan’s foreign trade. It shows the development opportunities of the Kyrgyz economy, the country’s main trading partners, and how these relations have evolved in recent years. The author presents the main export and import goods of Kyrgyzstan and describes its economy in terms of dependence on specific types of goods or economic partners and their impact on the country’s policy through trade.